2012
DOI: 10.15288/jsad.2012.73.531
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use at Time of Injury and Survival Following Traumatic Brain Injury: Results From the National Trauma Data Bank

Abstract: ABSTRACT. Objective: Premised on biological evidence from animal research, recent clinical studies have, for the most part, concluded that elevated blood alcohol concentration levels are independently associated with higher survival or decreased mortality in patients with moderate to severe traumatic brain injury (TBI). This study aims to provide some counterevidence to this claim and to further future investigations. Method: Incident data were drawn from the largest U.S. trauma registry, the National Trauma D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…The highest heterogeneity was noted between the studies by Chen et al 7 and Salim et al, 37 with an interstudy I 2 of 88% (c 2 = 8.54, p = 0.003). Two other studies that notably increased the heterogeneity were those by Talving et al 45 and Tien et al 47 These studies were excluded from the sensitivity analyses.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The highest heterogeneity was noted between the studies by Chen et al 7 and Salim et al, 37 with an interstudy I 2 of 88% (c 2 = 8.54, p = 0.003). Two other studies that notably increased the heterogeneity were those by Talving et al 45 and Tien et al 47 These studies were excluded from the sensitivity analyses.…”
Section: Resultsmentioning
confidence: 87%
“…From the chosen abstracts a total of 11 full-text articles were fully reviewed. 1,3,4,6,7,22,37,38,41,45,47 Individual study characteristics are shown in Table 1. All studies included were considered to be of high quality by the Newcastle-Ottawa quality assessment scale ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations